THE EXISTENCE OF TRADITIONAL VILLAGES IN THE STATE CONSTRUCTION OF THE REPUBLIC OF INDONESIA - I Gusti Ngurah Sudiana; Nuriawan, I Nengah Alit (UHN I Gusti Bagus Sugriwa Denpasar, 2025)
This study aims to analyze the existence of the Traditional Village in the Provincial Government of Bali. This research was conducted in two districts in Bali, namely Bangli and Karangasem. Data collection in this study was carried out through observation, in-depth interviews, and documentation studies. Based on the research conducted, it was found that, the differences in the structure of traditional village leaders can be described in two types, namely the traditional village version of the leadership structure of the Bali Aga traditional village and the version of the Balinese Majapahit traditional village. The Bali Aga traditional village referred to in this study is the Tenganan Pagringsingan Traditional Village, Manggis sub-district, Karangasem district, and the Batur Traditional Village, Kintamani Bangli, representing the Bali Aga Traditional Village. Meanwhile, the Kubu Traditional Village, Bangli District, Bangli Regency, and Karangasem Traditional Village, Karangasem District, Karangasem Regency, represent the Balinese Majapahit/apanage traditional village. Bali Aga traditional villages are found in the mountainous areas of the Bangli, Karangasem, Tabanan, and Singaraja districts. Regarding the term Bali Mula Traditional Village or Bali Aga, Balinese customary law experts still do not have an agreement as a unified word term for the name of the Traditional Village whether it is Bali Aga/Bali Mula, Bali Apanaga, and so on. In this research, the name used for the term Balinese Traditional Village as it is found in the area mentioned above is the Bali Aga Traditional Village. Meanwhile, villages other than Bali Aga Village are called Bali Apanaga.